Penerapan E-learning dalam Pembelajaran Bahasa Arab di Masa Pandemi - Ahmad Fadilah Khomsah; Muassomah Muassomah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
Today's online-based media learning innovations are increasing. In the world of education in Indonesia, there has been a shift in the tradition of learning from school-based offline to online technology-based, as a result of the Covid-19 pandemic. This study examines the application of E-learning in Arabic learning in class X IPS 3 MAN 3 Tulungagung. This study aims to determine the application of the use of E-learning in learning Arabic along with its benefits, driving and inhibiting factors. So that later the problems and shortcomings can be overcome. The method used is descriptive qualitative, data collection using observation, interviews and documentation. The results of this research are obtained first, in its application there are several kinds of online-based media used such as Web base learning, Zoom meeting rooms, WhatsApp, Ebook, and Google. Second, the application of Arabic learning during the pandemic was very helpful in overcoming the problems of implementing learning outside the network which was disrupted due to the corona virus outbreak. Third, there are several factors that encourage and hinder the successful implementation of online-based learning such as the internet network, the availability of communication tools, facilitators and control from teachers and parents to students. In addition there are factors that become obstacles, such as the lack of socialization on the use of E-learning, problematic internet networks, inadequate communication tools and lack of control from parents to students.